CalArts : Skeptical Belief(s). - The Renaissance Society at the University of Chicago; Newport Harbor Art Museum, Newport Beach (Chicago : The Renaissance SOciety at the University of Chicago, 1987)
Affarian, Carl ; Bachman, Gary ; Balk, Dennis ; Bernard, Cindy ; Bickerton, Ashley ; Bleckner, Ross ; Bloom, Barbara ; Brauntuch, Troy ; Brenner, Beth ; Cabrera, David ; Casebere, James ; Chow, David ; Cypis, Dorit ; Duff, Dana ; Ebner, Tim ; Ericson, Kate ; Ziegler, Mel ; Fischl, Eric ; Franklin, John ; Giegerich, Jill ; Goldstein, Jack ; etc.
CalArts : Skeptical Belief(s), The Renaissance Society at The University of Chicago, May 6 - June 27, 1987 / Newport Harbor Art Museum, Newport Beach, January 24 - March 20, 1988
boek